2018
DOI: 10.1016/j.sjbs.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mathematical modeling of infrared thin-layer drying of garlic slices

Abstract: Drying of garlic slices in thin-layer have been studied with Infrared (IR) at 0.075, 0.15, 0.225 and 0.3 W cm radiation intensity and 0.75 and 1.25 m s air flow velocity. The results showed increasing in drying rate and decreasing at the time of drying with decreasing air flow velocity and increasing IR radiation intensity. The effective moisture diffusivity (D) was obtained using Fick's diffusion equation and its mean values ranged between 5.83×10 and 7.66×10 m s for all investigated conditions. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
74
1
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 32 publications
12
74
1
3
Order By: Relevance
“…The results were in accord with the seminal study conducted by Roberts et al (), where it was suggested that the drying process of most food materials including grape seeds occurs predominately in falling rate period. Convergent results were observed in the drying process of food materials (Avhad & Marchetti, ; Younis et al, ). Based on the results, the findings have provided the insights on the effect of drying temperature on moisture loss, which is a prominent parameter in drying and quality considerations for industrial applications of Kyoho seeds.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…The results were in accord with the seminal study conducted by Roberts et al (), where it was suggested that the drying process of most food materials including grape seeds occurs predominately in falling rate period. Convergent results were observed in the drying process of food materials (Avhad & Marchetti, ; Younis et al, ). Based on the results, the findings have provided the insights on the effect of drying temperature on moisture loss, which is a prominent parameter in drying and quality considerations for industrial applications of Kyoho seeds.…”
Section: Resultsmentioning
confidence: 87%
“…However, the goodness of fit statistical results, such as χ2 , RMSE, %E, and SSE (Table ) was used to represent the quality of fit. The best suitable model was selected based on the combination of higher R 2 and lower χ2 , RMSE, %E, and SSE (Vega‐Gálvez et al, ; Younis et al, ). It was noticed that the R 2 values for the models ranged from 0.8587 to 1 at all temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations